National venture competition and technopreneurship development in Malaysia / Wee-Liang Tan, Karl Egge and Osman Mohamad (Faculty of Business and Management ; UiTM Press, 2005)
In the global slowdown, there is a revived interest in entrepreneurship development particularly in new startups based on technology. Many countries see this as a basis for future growth and competitiveness. To encourage technology-based entrepreneurship, also called entrepreneurship, business plan competitions could be one strategy. Typically one finds business plan competitions either for members of a region of a country (e.g., SW Pennsylvania); or, as an extension of University programs in business and entrepreneurship (e.g., MIT). Certainly such competitions can generate and exploit interest in entrepreneurs/up. In Malaysia, beginning in 2001, a business plan competition with a difference has been established. It is not organized to draw participation from educational institutions. It was not a competition initiated by venture capitalists, but a national effort. The three parties organizing it included a consulting firm (McKinsex), a stock exchange (Mesdaq/ KLSE), and a nonprofit business organization (the Malaysian Institute of Management). Of course it had the support of the government and many others. Its goal is to show-case technology oriented new startups to suppliers of capital and to suppliers of know how and who. But its goal also is to help foster an entrepreneurial buzz in the nation. In this sense, it is a national business plan competition that merges three functions: a business plan competition, a venture capital forum, and a network building venue. The paper considers the case for such a competition, and reports on who were the initial contestant participants.